A Phenomenology of Social Stances - Gian Paolo Terravecchia (Phenomenology and Mind, 2016)
The paper develops a phenomenology of social stances, trying to show that Margaret Gilbert’s work on joint commitments can be understood as a special case of what here presented. The offered conceptualization shows that “to accept” is an important moment of social reality (as in Gilbert’s work), but also that there are many more stances to be discussed which are important. These are “to refuse” (or “to rebel against”), “to suffer”, “to assent” and “to make something one’s own”. The last part of the paper tests the explanatory power of the sketched theory, trying to show that it provides valuable elements for an account of convention.